Strategic Approach to Innovation Management and Strategic Changes to Improve Innovation Management - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Innovation can be described as developing new ideas and processes that aims to create new products or improving business processes. Organizations today looks into the concept of innovation as a way to increase value and develop new ways of doing business. On the other hand, adopting an innovation requires strategic management approaches in order to ensure that the current innovation implementations will yield significant improvements. With innovation comes change and organizations will need not only to adopt innovative processes, but should also be able to implement change; this is when innovation management becomes apparent. Every organization adopt innovation approach of varying scale such modest, moderate, and strong. From each approach strategies can be derived depending on the how the innovation will be used and how it will impact the organization as a whole. In the case of Oman, different strategies were created to leverage on the capabilities of an organization. Some organizations form partnerships to achieve a common goal and to create a platform in which managing the implemented innovation becomes a shared responsibility of the partnering organizations. In some cases, strategies employed in innovation management is being done to accelerate development as a form of innovation improvement outcome.